Knowledge service engineering handbook - Kantola, Jussi; Karwowski, Waldemar, 1953- (Boca Raton, Fla. : Taylor & Francis, 2012)
"Preface Knowledge service engineering is an emerging field in the scientific and application worlds, focusing on the joint systems of data networks, information networks, and human knowledge networks. It aims at acquiring and utilizing data, information, and human knowledge to produce high-performance joint knowledge services to support the knowledge economy of the twenty-first century. Knowledge service engineering provides practical knowledge as a service to citizens, end users, industrial customers, companies, organizations, and governments. This new subdiscipline aims at developing and maintaining sustainable knowledge services globally. Acquiring and utilizing data, information, and human knowledge networks require different types of engineering, which inspire, in many exciting ways, the creation of sustainable knowledge services for the future. The aim of this handbook is to present the recent advances in knowledge service engineering by accomplished researchers and practitioners from around the world. We hope that it will be helpful for researchers and students in the field, as well as to professionals who develop a variety of innovative knowledge services. We project that many college students will become knowledge service professionals shortly after completing their studies"--
pt. 1. Introduction to knowledge service engineering -- pt. 2. Engineering from data, information, and knowledge toward services -- pt. 3. Human networks in knowledge services -- pt. 4. High-performance knowledge service systems.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Expert systems (Computer science); Information technology; Knowledge management; Electronic books